Essentials of Pain Management - Vadivelu, Nalini; Urman, Richard D.; Hines, Roberta L.; SpringerLink (Online service) (New York, NY : Springer New York, 2011)
Essentials of Pain Management is a concise, evidence-based guide that stresses a multidisciplinary approach to pain and provides a thorough review of clinical principles and procedures. Edited by faculty from Yale and Harvard Medical Schools, Essentials provides a practical approach to pain management for every type of pain management practitioner. Features: * Extensive case vignettes illustrating specific pain management challenges and solutions * Multiple-choice questions with detailed answers useful for exam preparation * In-depth discussions of palliative medicine, end-of-life care, physical therapy and acupuncture, behavioral therapy, and pediatric and elderly pain * A formulary of commonly used drugs for an easy go-to reference for every office * Special considerations for nurses and dentists From career choices in pain management to the specific drugs, procedures, and therapies that can alleviate pain, Essentials of Pain Management is a valuable resource for all pain management practitioners.
Part 1. Introduction -- 1. Introduction to Pain Management, Historical Perspectives, and Careers in Pain Management -- 2.Multidisciplinary Approach to Pain Management -- Part 2. Anatomy and Physiology -- 3.Anatomic and Physiologic Principles -- 4.Acute and Chronic Mechanisms of Pain -- Part 3. Clinical Principles -- 5.Assessment of Pain: Complete Patient Evaluation -- 6.Diagnostic Testing in Pain Management -- Part 4. Pharmacology -- 7.Opioids: Pharmacokinetics and Pharmacodynamics -- 8.Opioids: Basic Concepts in Clinical Practice -- 9.Non-opioid Analgesics in Pain Management -- 10.Alternative and Herbal Pharmaceuticals -- 11.Importance of Placebo Effect in Pain Management -- Part 5. Non-pharmacologic Management of Pain -- 12.Psychological and Psychosocial Evaluation of the Chronic Pain Patient -- 13.Interventional Pain Management -- 14.Functional Restoration of Patients with Pain -- 15.Occupational Therapy in Client-Centered Pain Management -- 16.Acupucture -- 17.Nursing Perspective on Pain Management -- 18.Post-surgical Pain Management -- Part 6. Acute Pain Management -- 19.Surgical and Trauma Patient and Burns -- 20.Regional Anesthesia Techniques -- 21.Principles of Ultrasound Techniques -- 22.Labor Pain Management -- Part 7. Chronic Pain Management -- 23.Neuropathic Pain -- 24.Ischemic and Visceral Pain -- 25.Fibromyalgia, Arthritic, and Myofascial Pain -- 26.Head, Neck, and Back Pain -- 27.Headache -- 28.Management of Cancer Pain -- 29.Ethics in Pain Management and End of Life Care -- Part 8. Additional Topics -- 30.Pediatric Pain Management -- 31.Managing Pain in the Addicted Patient -- 32.Pain Management in Elderly Patients -- 33.Management of Oro-Dental Pain -- 34.Drug Formulary for Pain Management -- Appendix -- Multiple Choice Questions.
Keywords: Medicine; Anesthesiology; Family medicine; Neurology; Pain Medicine; Medicine & Public Health; Anesthesiology; Pain Medicine; General Practice / Family Medicine; Neurology